Individual Counselling Rational Emotive Behavior Therapy to Overcome Anxiety in Adolescent Victims of Sexual Violence - Cania, Lita Fitara; Karneli, Yeni (Department of Guidance and Counseling, FIP, Undiksha, 2024)
This study is motivated by the occurrence of sexual violence against young women today which is carried out by force by the perpetrator. The compulsion has a negative impact that causes anxiety disorders, both physiological anxiety symptoms and cognitive symptoms. With individual rational emotive behavior therapy counseling, irrational beliefs and actions can be changed into rational ones using the ABCDE theory. The purpose of this study is to apply individual rational emotive behavior therapy counseling interventions to provide positive and effective effects to overcome the anxiety of young victims of sexual violence. This type of research is quantitative experimental method using a single subject research design. The subject in the study was 1 person with purposive random sampling, namely young victims of sexual violence who were identified as anxious, to analyze the subject with repeated treatment implementation at a specified time. The method used in collecting data is observation and administration of the anxiety scale. The data analysis technique in this study uses quantitative statistics with descriptive analysis and analysis in conditions and between conditions. The results of this study are based on analysis in conditions and between conditions of the subject at baseline and intervention conditions giving a positive effect so that the findings in this study by applying individual rational emotive behavior therapy counseling interventions are effective in overcoming the anxiety of young victims of sexual violence.